2023
DOI: 10.1155/2023/1571991
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Chemical Characterization of Biosurfactant Produced from a Novel Pseudomonas guguanensis Strain Iraqi ZG.K.M

Abstract: Microbial surfactants are widely used in medical, pharmaceutical, agricultural, industrial, food, and cosmetics applications. In the present study, 85 indigenous bacteria were isolated from petroleum-contaminated soils of the Al Dourah refinery, electric power station, and electric generators in Baghdad, Iraq. Twenty nine isolates gave positive results in both blood agar and blue agar medium and were secondarily screened. One isolate was selected as a potent biosurfactant producer and molecularly identified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
(104 reference statements)
2
16
0
Order By: Relevance
“…These findings bear conformity with those obtained by Piegza et al (2021), where they reported the main components of fatty acids, including 3-hydroxy-stearic acid (C18:0), 3-hydroxypalmitic acid (C16:0), acid octadecene (C18:1, double bond in position 2) represent the biosurfactant moiety in Trichoderma citrinoviride HL and C1 supernatants. Also, fatty acids; n-hexadecanoic acid, methyl linoleate, ethyl palmitate, 8-octadecenoic acid, methyl stearate, methyl ester, ethyl stearate, dodecanoic acid, methyl palmitate, linoleic acid, 9,17-octadecadienal and 2,4-ditert-butylphenol were showed in culture filtrate of Pseudomonas guguanensis Strain Iraqi ZG.K.M by Ghazi et al (2023).…”
Section: Discussionmentioning
confidence: 93%
“…These findings bear conformity with those obtained by Piegza et al (2021), where they reported the main components of fatty acids, including 3-hydroxy-stearic acid (C18:0), 3-hydroxypalmitic acid (C16:0), acid octadecene (C18:1, double bond in position 2) represent the biosurfactant moiety in Trichoderma citrinoviride HL and C1 supernatants. Also, fatty acids; n-hexadecanoic acid, methyl linoleate, ethyl palmitate, 8-octadecenoic acid, methyl stearate, methyl ester, ethyl stearate, dodecanoic acid, methyl palmitate, linoleic acid, 9,17-octadecadienal and 2,4-ditert-butylphenol were showed in culture filtrate of Pseudomonas guguanensis Strain Iraqi ZG.K.M by Ghazi et al (2023).…”
Section: Discussionmentioning
confidence: 93%
“…The color of biosurfactants generally varies according to the producing strain, the culture media composition and the extraction technique. The colors reported in the literature were either whitish, yellowish or brownish [64]. Fig.…”
Section: Color Of Biosurfactantsmentioning
confidence: 93%
“…Methylene blue is sometimes added in the culture media to ease the observation of the precipitation line materialized as a blue halo around well containing culture [52]. This method was successfully used to confirm the anionic nature of biosurfactants derived from Lactococcus lactis [63], E. faecium [51], and Pseudomonas guguanensis strain Iraqi ZG.K.M [64]. However, the method is not suitable for other types of biosurfactants such as lipopeptides or glycoproteins.…”
Section: Identification Of Ionic Properties Of Biosurfactantsmentioning
confidence: 99%
See 2 more Smart Citations